Identifikasi Miskonsepsi Siswa pada Konsep Substansi Genetik dengan Menggunakan Three Tier Test di Kelas XII Sekolah Menengah Atas - Fariani Madukubah; Mushawwir Taiyeb; Hartati Hartati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
This research is a descriptive study that aimed to provide information of (1) percentage of students’misconceptions, not understanding the concept, and understanding the concept (2) factors causingmisconception (3) sub-concept with the highest misconception on concept of genetic substance using three tiertest. Population in this research is all student of class XII SMAN 2 Makassar, sample of research is student ofclass XII IPA 1 counted 35 people. The instrument used is three tier test which amounts to 25 items. Data wereanalyzed descriptively by using the category made by Pesman and Eryilmaz to determine students’understanding. Students were observed and interviewed to obtain data about factors that caused misconception.The result of data analysis of three tier test showed that 29.94% experienced misconception, 42.29% do notunderstand concept, and 27.77% understand concept. The highest percentage of students’ misconceptions isfound in the gene and allele sub concept by 57.15%. Factors that causing misconception are student that havewrong reasoning due to incomplete information, lack of interest in learning certain concept, the absence ofteacher confirmation after learning process, teacher that describing concept too fast, and text book that used inlearning process contain several misinformation.